OGHUZ DIALECT ELEMENTS IN "DEVANI NIHANI" - Sherzod Khojamberdiyev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the reasons for the use of linguistic elements belonging to the Oghuz dialect and their arrival in the text of the poems in some of the ghazals of the “Devoni Nihoniy”, one of the first works of the famous poet, adib, playwright, publicist Hamza Hakimzoda Niyazi, are covered in relevant examples. The article reflects on the words belonging to the Oghuz dialect, which the poet used mainly in his jokes.